1979
DOI: 10.1002/ana.410050302
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic opening of the blood‐brain barrier and local cerebral glucose utilization

Abstract: The effects of osmotic opening of the blood-brain barrier (BBB) on local cerebral glucose utilization (LCGU) were studied in rats with the carbon 14-deoxyglucose method. The BBB was opened to Evans blue dye by unilateral carotid artery perfusion with hypertonic mannitol solution. (14C)-Deoxyglucose was injected 15 minutes or two to three hours later. Osmotic opening of the BBB resulted in focal areas of intense LCGU in affected areas of the perfused hemisphere. In the contralateral hemisphere, glucose utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…Pappius et al (1979) found decreases in cerebral blood flow on the order of 25-65% fol lowing BBB disruption. The obvious quantitative difference between their data and our own may partly be due to the considerably greater rate of infusion (2.49 ml 1.4 M mannitol in 30 s) used by these investigators.…”
Section: Discussionmentioning
confidence: 93%
“…Pappius et al (1979) found decreases in cerebral blood flow on the order of 25-65% fol lowing BBB disruption. The obvious quantitative difference between their data and our own may partly be due to the considerably greater rate of infusion (2.49 ml 1.4 M mannitol in 30 s) used by these investigators.…”
Section: Discussionmentioning
confidence: 93%
“…Unilateral opening of the blood-brain barrier in rats by unilat eral carotid injection with a hyperosmotic mannitol solution leads to widely distributed discrete regions of intensely increased glucose utilization in the ip silateral hemisphere (Pappius et al , 1979). These focal regions of hypermetabolism may reflect local regions of seizure activity.…”
Section: Pathophysiological Applicationsmentioning
confidence: 99%
“…This pattern of disturbance is indicative of either severe ischemia or mitochondrial dysfunction involving a block in NADH transport or utilization (32). Osmotic opening of the blood-brain barrier is accompanied by an initial increase in cerebral blood flow lasting up to 6 min (33), followed by a decrease in flow associated with a mild vasogenic brain edema lasting up to I h (34,35). During this time there is uncoupling of cerebral blood flow and metabolism.…”
Section: Discussionmentioning
confidence: 99%